Exploring the barriers to using assistive technology for individuals with chronic conditions: a meta-synthesis review - Howard, Jonathan; Fisher, Zoe; Kemp, Andrew H.; Lindsay, Stephen; Tasker, Lorna H.; Tree, Jeremy J. (Disability and rehabilitation: Assistive technology, 2022)
Assistive technology can provide a key tool to enabling independence, greater inclusion and participation in society for individuals with chronic conditions. This potential is currently not always realized due to barriers to accessing and using assistive technology. This review aims to identify the common barriers to acquiring and using assistive technology for users with chronic conditions through a systematic meta-synthesis. This differs from other systematic reviews by applying a transdiagnostic approach to identify if barriers are common across chronic conditions. A systematic literature search of five scientific databases (PubMed, SCOPUS, PsycINFO, CINAHL and Medline) was conducted to identify relevant qualitative studies. The search was conducted in November 2019. For the identified articles, thematic content analysis was conducted and the methodological quality was evaluated using the Critical Appraisal Skills Programme (CASP) checklist for qualitative research. Forty papers met the inclusion criteria and were included in the analysis. Fifty-one descriptive themes grouped into six overarching analytical themes were identified from the studies. The analytical themes identified were: the design and function of the assistive technology, service provision, information and awareness, psychological barriers, support network and societal barriers. The barriers are interconnected and common across different health conditions. More involvement in personalized care for developing strategies, adaptation of home technologies and provision of assistive technology could overcome the service provision and design barriers to assistive technology. Accessible information and providing greater awareness will be important to overcoming information, psychological and societal barriers to assistive technology. Implications for rehabilitation Individuals with chronic conditions face complex barriers to acquiring and using assistive technology as a result of the devices themselves, their individual context, the healthcare context where assistive technology is provided and wider societal barriers. The provision of assistive technology needs to change away from the traditional medical model of the "expert" clinician and instead focus on more user involvement to deliver personalised care that utilises the users lived knowledge and experiences. Assistive technology provision should be considered alongside how to adapt everyday mainstream technology to meet user needs; the provision of devices should encourage creative problem solving rather then relying on pre-defined prescription lists of assistive technology.